An appraisal to address health consequences of Vitamin D deficiency with food fortification and supplements: time to act! - Reichrath, Jörg; März, Winfried; Gruijl, Frank R. De; Vieth, Reinhold; Grant, William B.; Slominski, Andrzej T.; Holick, Michael F.; Vogt, Thomas; Pilz, Stefan (Anticancer research, 2022)
A symposium entitled “Vitamin D in Prevention and Therapy” was held on May 4-5, 2022, in Homburg, Germany to discuss important new advances in the field, including identification of new vitamin D signaling pathways, of new biologic effects of vitamin D-compounds (e.g., on the microbiome), and convincing proof of the relevance of vitamin D deficiency for the risk and outcome of many chronic diseases, including cancer, cardio-vascular, auto-immune, metabolic, and infectious diseases. Concerning the COVID-19-pandemic, an inverse association between 25(OH)D serum concentrations and SARS-CoV-2-infections, morbidity, and mortality was shown. In relation to cancer, several meta-analyses recently demonstrated an association of vitamin D-supplementation with significantly decreased mortality rates, which presumably would reduce health care costs. Considering the impressive body of evidence and the high safety of oral supplementation and food fortification with vitamin D, it was concluded that there is now an urgent need to act. In many countries worldwide, health care authorities need to increase efforts to address vitamin D deficiency, e.g., via food fortification and/or supplementation with vitamin D, and/or promoting moderate UV-exposure. It was estimated that in many countries, vitamin D intakes of the order of appr. 1,000 IE (25 μg)/day would be needed to bring and/or keep the vast majority of people over a serum 25(OH)D threshold of 20 ng/ml (50 nmol/l), which would be difficult to obtain alone from food fortification. New developments in personalized medicine may represent helpful tools to identify populations at risk for vitamin D deficiency and their responsiveness to vitamin D treatment.